Genetic Analysis of MEFV Gene Pyrin Domain in Patients With Behçet's Disease - Ahmet Dursun; Hatice Gul Durakbasi-Dursun; Ayse Gul Zamani; Zerrin Gülin Gulbahar; Recep Dursun; Cengiz Yakicier (Mediators of Inflammation)
Objectives. Behçet's disease (BD) is a systemic vasculitis with recurrent oral and genital ulcers and uveitis. MEFV gene, which is the main factor in familial Mediterranean fever (FMF), is also reported to be a susceptibility gene for BD. The pyrin domain of MEFV gene is a member of death-domain superfamily and has been proposed to regulate inflammatory signaling in myeloid cells. This study was designed to determine if mutations in pyrin domain of MEFV gene are involved in BD. Methods. We analyzed the pyrin domain of MEFV gene in 54 Turkish patients with BD by PCR-analysis and direct sequencing. Results. Neither deletion or insertion mutations nor point mutations in pyrin domain were found in any patient. Conclusion. Although pyrin gene mutations have been reported in patients with BD, pyrin domain is not mutated. However, alterations in other regions of MEFV gene and interaction between pyrin domains are needed to be further investigated.